Исследование тормозных режимов частотно-регулируемого электропривода с помощью виртуальных моделей - Чермалых, Александр Валентинович; Майданский, Иван Ярославович (НТУ "ХПИ", 2013)
The possible structure of the braking modules asynchronous electric drive with frequency regulation. With the help of virtual models of investigate the behavior of the system during braking. We obtain the diagram by the angular velocity and the electromagnetic torque of the motor as well as graphs of variation energy performance. According to the simulation results, a comparative analysis and gives recommendations regarding the application of various design options for braking units with their advantages and disadvantages.
Keywords: электромеханические системы; компьютерное моделирование; пакеты прикладных программ; тормозной резистор; управляемая вентильная группа; активный выпрямитель